Change and continuity at the world bank : reforming paradoxes of economic development - Hammer, Peter J. (Cheltenham Edward Elgar Publishing Ltd., 2013)
Summary from Elgaronline: "This fascinating book examines the World Bank's capacity for change, illustrating the influence of overlapping political, organizational and epistemic constraints. Through comprehensive historical and economic analysis, Peter J. Hammer illuminates the difficulties faced by recent attempts at reform and demonstrates the ways in which the training and socialization of Bank economists work to define the policy space available for meaningful change."
1. The world bank and wolfensohn era reforms -- 2. The ABCs of the world bank -- 3. A framework for modeling bank behavior -- 4. The dynamics of epistemic economic change -- 5. Application to debt relief, participation and knowledge -- 6. Application to social capital -- 7. Application to institutional economics -- 8. Redefining bank research within the epistemic constraints of economics -- 9. Bank evolution since wolfensohn -- 10. The future of development --
Includes bibliographical references and index
Keywords: International banking; WORLD BANK; INTERNATIONAL BANKING; ECONOMIC DEVELOPMENT